2009
DOI: 10.1111/j.1475-097x.2008.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in left ventricular ejection time and pulse transit time derived from finger photoplethysmogram and electrocardiogram during moderate haemorrhage

Abstract: Shortening of LVET(p) from 303+/-2 to 293+/-3 ms (mean+/-SEM; P<0.01) and prolongation of PTT from 177+/-3 to 186+/-4 ms (P<0.01) were observed in 81% and 91% of subjects respectively when comparing PRE and POST. During blood donation, progressive blood loss produced falling trends in LVET(p) (P<0.01) and rising trends in PTT (P<0.01) in FIRST and SECOND, but a falling trend in RRi (P<0.01) was only observed in SECOND. Monitoring trends in timing variables derived from non-invasive ECG and finger PPG signals m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
(115 reference statements)
1
10
0
Order By: Relevance
“…Further investigations are required to test the methodology in detecting small blood loss. However, this can be seen from previous papers [5-6, 20] which have used blood donation for research. Although the amount of blood loss during blood donation is relatively small, it is sufficient to cause a reduction in circulatory blood volume and it has been shown that the changes of PTT over time may still be useful for detecting ongoing blood loss in the initial phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations are required to test the methodology in detecting small blood loss. However, this can be seen from previous papers [5-6, 20] which have used blood donation for research. Although the amount of blood loss during blood donation is relatively small, it is sufficient to cause a reduction in circulatory blood volume and it has been shown that the changes of PTT over time may still be useful for detecting ongoing blood loss in the initial phase.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hemodynamic monitoring methods are sensitive to blood loss, however, methods such as real-time arterial catheterization and central venous catheterization are invasive and can cause damage potentially. Several recent studies have found non-invasive PTT method as a reliable technique that can be derived from photoplethysmographic (PPG) pulse oximetry waveform and ECG to indentify blood volume changes in awake healthy subjects [6]. The purpose of this paper is to utilize the PTT non-invasive measurement such as ECG and PPG pulse oximetry waveforms for creating reliable indicator to blood loss during surgical operation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies were able to show the ability to measure LVET using different technologies including Photoplethysmographic Pulse Oximeter [6,12], or PE sensors [5,9]. However, unlike the setting in the current research, in most of the studies, the sensor is attached to the participant's body, a setup that produced a signal with a relatively high signal to noise ratio.…”
Section: Discussionmentioning
confidence: 99%
“…4) Normalized Pulse Transmit Time (PTT): Pulse transmit time is the time it takes from the onset of the left ventricle depolarization to the time the blood reaches the peripheral arteries and is measured as the interval between the R peak in ECG signal and the next PPG trough as shown by t RS in Fig. 2 [29]. The pulse transmit time is related to pulse wave velocity or the speed of blood flow in arteries.…”
Section: A Data Analysismentioning
confidence: 99%